Effects on rat testes of the thiosemicarbazone derivative Schiff base (4-(1-phenylmethylcyclobutane-3-yl)2-(2-hydroxybenzylidenehydrazino)thiazole) and its cadmium(II) complex - Öner, H; Karatepe, M; Karatas, F; Öner, J; Yilmaz, I; Cukurovali, A (Wiley, 2005)
The aim of this study was to investigate structural and biochemical changes in testes of rats treated with the thiosemicarbazone derivative thiazole ring Schiff base, (4-(1-phenyl-methylcyclobutane-3-yl)-2-(2-hydroxybenzylidene-hydrazino) thiazole (L), and its Cd(II) complex (CdL2). The animals were divided into three groups. Group I was designated as control. The rats in groups II and III were injected subcutaneously with L or CdL2 respectively at 150-mg kg(-1) doses at 3-day intervals for 15 days. At the end of the study, blood samples were collected for biochemical analysis, and testes were removed for histological examinations. Serum levels of vitamin A, E and MDA of the L-injected group were similar to the control group. While CdL2 treatment decreased serum vitamin A and E levels, it increased the MDA level compared to other groups. Histologically, the testes structures of L-treated animals were similar to the control. Spermatogenic cells in seminiferous tubules of CdL2-treated animals displayed necrosis. Nuclei of spermatogonia and primary spermatocytes were pyknotic and heterochromatic. Homogenous pink particles were present in place of the spermatids. The interstitial areas were oedematous and intertubular vessels were plugged. In conclusion, the present results indicate that L does not cause biochemical and morphological alterations, but its Cd(II) complex has degenerative effects in normal rat testes. Copyright (c) 2004 John Wiley & Sons, Ltd.
Keywords: rat; Schiff base; testes; thiosemicarbazone